Immune Targeting of Tetraspanins Involved in Cell Invasion and Metastasis - Vences-Catalán, Felipe; Levy, Shoshana (Frontiers in Immunology, 2018)
Metastasis is the ultimate consequence of cancer progression and the cause of patients’ death across different cancer types. Patients with initial diagnosis of distant disease have a worst 5-year survival compared to patients with localized disease. Therapies that target primary tumors fail to eradicate distant dissemination of cancer. Recently, immunotherapies have improved the survival of patients with metastatic disease, such as melanoma and lung cancer. However, only a fraction of patients responds to immunotherapy modalities that target the host immune system. The need to identify new druggable targets that inhibit or prevent metastasis is, therefore, much needed. Tetraspanins have emerged as key players in regulating cell migration, invasion, and metastasis. By serving as molecular adaptors that cluster adhesion receptors, signaling molecules, and cell surface receptors; tetraspanins are involved in all steps of the metastatic cascade. They regulate cell proliferation, participate in EMT transition, modulate integrin-mediated cell adhesion, and participate in angiogenesis and invasion processes. Tetraspanins have also been shown to modulate metastasis indirectly through exosomes and by regulating cellular interactions in the immune system. Importantly, targeting individual tetraspanin with antibodies has impacted tumor progression. This review will focus on the contribution of tetraspanins to the metastatic process and their potential as therapeutic tumor targets.